Recombinant expression of cyclotides using expressed protein ligation - Campbell, Maria Jose (Methods Mol Biol, 2020)
Cyclotides are naturally-occurring micro-proteins (≈30 residues long) present in several families of plants. All cyclotides share a unique head-to-tail circular knotted topology containing three disulfide bridges forming a cystine knot topology. Cyclotides possess high stability to chemical, physical and biological degradation and have been reported to cross cellular membranes. In addition, naturally-occurring and engineered cyclotides have shown to possess various pharmacologically-relevant activities. These unique features make the cyclotide scaffold an excellent tool for the design of novel peptide-based therapeutics by using molecular evolution and/or peptide epitope grafting techniques. In this chapter, we provide protocols to recombinantly produce a natively folded cyclotide making use of a standard bacterial expression system in combination with an intein-mediated backbone cyclization with concomitant oxidative folding.